Come Hell or High Fever Readying the World's Megacities for Disaster - Glenn, Russell W (ANU Press, 2023)
Nations appear and fall, but cities endure and rediscover how to succeed. In this meticulously defined and researched book, Glenn presents ideas for minimising suffering during urban catastrophes. His urgency identifies risks held in urban areas by 3.5 billion people. These people are many of us: as urban populations occupying 3 per cent of our planet's land area, drawing water from 41 per cent of the world's ground surface, consuming 60 to 80 per cent of global energy and achieving 80 per cent of the world's economic productivity. For Glenn, our resilience-through diversity in preparation, survival and recovery-includes comprehensive approaches that are sustained in duration, orchestrated in bringing all necessary capabilities to bear, layered in approach and early in application.' -Major General Chris Field, Australian Army 'The time to prepare for the inevitable is now. Dr Glenn has written a book that should be read by all leaders, planners and responders who may be called upon in an urban disaster, whether natural or man-made. Military leaders should give it particular attention, as the human race is increasingly concentrated in its cities. Understanding how to wage war in dense urban terrain is essential, especially if a nation also seeks to hold the moral high ground. The fruits of any victory won among people that fails to consider the lessons in Come Hell or High Fever are likely to be very bitter.' -Lieutenant General Sean MacFarland, United States Army (retired)